Changes in negative urgency, positive urgency, and sensation seeking across adolescence. (February 2016) - Littlefield, Andrew K.; Stevens, Angela K.; Ellingson, Jarrod M.; King, Kevin M.; Jackson, Kristina M.
Abstract: The development and potential co-development of traits related to impulsivity and sensation seeking across adolescence has garnered substantial attention within the extant literature. Some prior research suggests that facets show distinct patterns of change across adolescence and that intraindividual changes in these traits may be unrelated. However, the extant literature is somewhat hampered by measurement issues and inconsistent findings. Using an accelerated longitudinal design in a sample of adolescents ( n = 1018; ages 11–16), changes in negative urgency, positive urgency, and sensation seeking were examined. The three facets showed similar trajectories across time (i.e., increasing during early adolescence before leveling off). Across all facets, there was strong evidence of correlated change, suggesting these traits are, developmentally, strongly related phenomena. Highlights: Piecewise latent growth curve modeling was utilized to model patterns of personality change across adolescence. There was strong evidence that negative urgency, positive urgency, and sensation seeking change correlated from ages 11–16. These constructs appear to be strongly related, rather than distinct, factors, during adolescence.